Mindfulness-based online intervention on mental health among undergraduate nursing students during coronavirus disease 2019 pandemic in Beijing, China: A randomized controlled trial - Dai, Zhenwei; Jing, Shu; Wang, Hao; Xiao, Weijun; Huang, Yiman; Chen, Xu; Fu, Jiaqi; Pan, Chen; Tang, Qiuping; Wang, Huan; Su, Xiaoyou (Frontiers in Psychiatry, 2022)
Objective To evaluate the effect of mindfulness intervention on improving mental health among undergraduate nursing students during the COVID-19 pandemic in China. Methods An online mindfulness intervention course Mindfulness Living With Challenge (MLWC) was developed by the research team and a randomized controlled evaluation of the intervention in undergraduate nursing students aged over 18 years was carried out. After the baseline survey, participants were randomized into control (56 students) and intervention groups (52 students). Pre- and post-intervention self-administered questionnaire surveys on depression, anxiety, stress, mindfulness, and perceived social support were performed. After the intervention, the acceptance of the online mindfulness course was assessed employing the theory of technology acceptance model. Results Compared with the control group, the reduction of anxiety and stress symptoms, as well as the improvement of mindfulness level and perceived social support in the MLWC intervention group were statistically significant(P<0.05), while the change in depression was not statistically significant. The scores of the five dimensions in TAM ranged from (5.88±0.94) to (5.91±0.97). Conclusion Online mindfulness intervention implemented in this study is effective in improving mental health among undergraduate nursing students, and they were interested in this intervention. Trial registration Chinese Clinical Trial Registry (ChiCTR), ChiCTR2200058103; Registered on March 29, 2022, http://www.chictr.org.cn/showproj.aspx?proj=136413.